Pengaruh Suhu Sintesis Katalis Partikel Ceria Zirconia terhadap Efektivitas Proses Delignifikasi - Okky Putri Prastuti; Fandi Angga Prasetya; Ufafa Anggarini; Rifqi Putera Herwoto; Hesty Rahayu (Politeknik Negeri Malang, 2020)
Biomass is organic material produced through photosynthetic processes. The presence of lignin on the cell wall will inhibit cellulose to be converted into products. Delignification will open the lignocellulose structure to make cellulose more accessible. The delignification process can be done by adding the Ceria-Zirconia catalyst to the biomass sample. The aim of this research is to determine the effect of synthesis temperature on Ceria Zirconia synthesis and to investigate the ability of Ceria Zirconia as a biomass delignification catalyst. Ceria- Zirconia Catalyst can be produced through the batch hydrothermal method. The precursors used were chemical solutions in the form of Ce(NO3)3.6H2O and ZrO(NO3)2.2H2O 0.06 M with a ratio of 1: 1, the synthesis temperature variables used were of 180oC, 200oC dan 220oC. Ceria Zirconia Catalysts will then be analyzed for their abilities through a 10 and 20 minute delignification process. The results showed that the increasing synthesis temperature will increase the ability of Ceria-Zirconia catalyst in the delignification process.